Modelling of photonic crystal fiber based on layered inclusions - Grujic, T; Kuhlmey, B; De Sterke, C; Poulton, C (Optical Society of American (OSA), 2009)
Photonic crystal fibers often consist of rotationally symmetric inclusions in an otherwise uniform background medium. The band diagrams and modes of such structures can be efficiently calculated using geometry-specific methods that exploit this rotational symmetry. Until now, these have only been applied to fibers in which the inclusions are circular and have a uniform refractive index. Here, we generalize this to arbitrary rotationally symmetric inclusions using a transfer matrix approach, and we implement this approach in an approximate scalar method, which is valid for low-index contrasts and in the rigorous Rayleigh multipole method. We apply the methods to structures incorporating inclusions with graded refractive indices and to structures incorporating metal rings. © 2009 Optical Society of America.